Because you're worth it? Determinants of Vice Chancellor pay in the UK. Issue 5 (30th July 2019) - Walker, James; Greve, Peder; Wood, Geoff; Miskell, Peter
Abstract: Wage inequality has increased across most developed nations; this has been manifested in a wide range of organisations and sectors, with implications for well‐being and sustainability; within UK universities, this has become increasingly visible. There is increasing pressure on universities to deliver social and economic impact in an increasingly market‐driven and metric‐driven environment. In the UK context, increasing financial pressure has led to both an escalation of student fees and constrained wage growth for faculty. In contrast, most Vice Chancellors have secured substantive pay packages raising concerns that regulatory failures may be contributing to the rise. We show that Vice Chancellors use their internal power within organisations to extract a disproportionate amount of the value created by the institution. However, we encountered much diversity according to the quality of governance, highlighting the extent to which not only contextual but also internal dynamics drive wage inequality.